ANALISIS CORROSION RATE TERHADAP REMAINING LIFE STORAGE TANK T03-300 KL DI PLTD POKA DENGAN MENGGUNAKAN METODE RISK BASED INSPECTION (RBI) - Rian Fazrian; Erwin B. Pattikayhattu; Alexander A. Patty (Journal Mechanical Engineering, 2024)
AbstractThis study is entitled "Corrosion Rate Analysis of Remaining Life Storage Tank T03-300 KL at PLTD Poka Using the Risk Based Inspection (RBI) Method". The purpose of this study is to evaluate the corrosion rate and residual life of the T03-300 KL storage tank used at PLTD Poka, as well as to provide recommendations related to appropriate inspection strategies based on risk analysis. The method used in this study is Risk Based Inspection (RBI), which allows the determination of the probability of failure (PoF) and the consequences of failure (CoF) of the storage tank. The data collected includes primary data through observation, measurement, and direct inspection of tanks, as well as secondary data from relevant literature.Keyword : Corrosion Rate, Remaining Life, Storage Tank Risk Based Inspection (RBI), Probability of Failure (PoF), Consequence of Failure (CoF)